REVITALISASI KRAME BANJAR DALAM MENANGKAL WACANA RADIKALISME DI LOMBOK BARAT - Nazar Naamy (Universitas Islam Negeri (UIN) Mataram, 2018)
The Krame Banjar has lost its place since independence in 1945 until the reform of 1998. The change of authority model that started from the charismatic authority (master teacher), traditional (traditional leader) to the rational-legal authority (government) made the Krame banjar metamorphose into village meetings (MUSDUS), village deliberation (MUSDES) led directly to the ruling village (legal-formal). The generations of Krame Banjar have been replaced by the formal legal generation which in fact, when deliberate it is not uncommon to expect the village budget (ADD) to move, unlike the banjar Krame based on kinship among banjars. Krame Banjar in West Lombok became an arena in revitalizing the discourse of radicalism that developments both locally and nationally. This paper will explain Krame Banjar as the early information system for the successor to ward off the current discourse of radicalism